2018
DOI: 10.3390/en11020279
|View full text |Cite
|
Sign up to set email alerts
|

Study on a Battery Thermal Management System Based on a Thermoelectric Effect

Abstract: Abstract:As is known to all, a battery pack is significantly important for electric vehicles. However, its performance is easily affected by temperature. In order to address this problem, an enhanced battery thermal management system is proposed, which includes two parts: a modified cooling structure and a control unit. In this paper, more attention has been paid to the structure part. According to the heat generation mechanism of a battery and a thermoelectric chip, a simplified heat generation model for a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…A battery thermal management system was investigated based on a thermoelectric effect [11]. In addition, an uncomplicated heat generation model for a cooling model and single battery cell were developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A battery thermal management system was investigated based on a thermoelectric effect [11]. In addition, an uncomplicated heat generation model for a cooling model and single battery cell were developed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an uncomplicated heat generation model for a cooling model and single battery cell were developed. It was concluded that the thermoelectric cooling combined with liquid cooling structure demonstrated better performance [11].…”
Section: Introductionmentioning
confidence: 99%
“…This paper selected a TAFEL-LAE895 100Ah ternary lithium ion power battery for study, and its main parameters are shown in Table 1 below: Calculation method was used to estimate the heat generated by the ternary lithium battery. At present, the commonly adopted calculation method is that supposing the internal material of the lithium ion battery generates heat uniformly [25,26]. The heat generation mechanism of the lithium ion battery was analyzed from two aspects, internal resistance heat generation and entropy increase reaction heat generation.…”
Section: Battery Calorie Calculationmentioning
confidence: 99%
“…In order to solve the problem that CPCM has limited thermal management capabilities, this paper introduces semiconductor refrigeration sheets, also known as TEC, using the Peltier effect of semiconductor material to carry heat from the cold terminal to the hot terminal [25,26]. A semiconductor refrigeration sheet is combined with the CPCM through heat pipe, and CPCM is cooled by its refrigeration function, such as is shown in Figure 11.…”
Section: Thermal Management Experiments With Combined Semiconductor Rementioning
confidence: 99%
“…The Seebeck effect results in an induced voltage in response to the temperature difference applied across the two ends of a thermocouple, where the induced voltage is directly proportional to the temperature difference [4,5]. The Peltier effect is the reverse of the Seebeck effect, and it results in cooling or heating at the two junctions of a thermocouple when an electric current passes through it [6]. The Peltier heat is directly proportional to the electric current, but its sign (cooling or heating) depends upon the direction of the electric current.…”
Section: Introductionmentioning
confidence: 99%